Pengaruh Kebijakan Perlakuan Selisih Kurs dalam Laporan Keuangan dan Indikator Keuangan Positif terhadap Laba pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Zefriyenni, Zefriyenni (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2018)
This study aims to test "The influence of the wise treatment of foreign exchange differences in financial statements and positive financial indicators on earnings in Pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2016. The population of this study were all Pharmaceutical companies listed on the Indonesia Stock Exchange in the 2012-2016 period. Samples used were 6 companies based on purposive sampling method. Data analysis method used is Multiple Regression using SPSS Version 21.0 for Windows software. Based on the empirical results of the study, it was found that (1) the foreign exchange difference did not have a significant effect on the profits of the pharmaceutical company. (2) Earning PerShare partially had a significant effect on the profits of the pharmaceutical company) Changes in Revenue partially have no significant effect on the profits of Pharmaceutical companies. Variables Exchange rates, EPS, Changes in Revenue, TAK together - influence the sigmifikan of company profits, with a contribution of 84.6% while the remaining 15.4% is influenced by other variables not examined.